(untitled) (Journal of Parents and Teachers, 1996)
The Barco de Vapor collection celebrates its 15th anniversary, highlighting its impact on children’s literature and the promotion of reading among children. It has published more than one million copies, with a variety of genres and quality authors. Its evolution over the years highlights the importance of literature in children’s development.